Participatory literacy practices: Creating possibilities - Pat Campbell (Adult Education Research Conference, 1995)
This paper outlines the design of an eight month doctoral study on participatory literacy practices in five adult literacy programs and touches upon some of the possibilities and their implications in the field of adult literacy.